PENGARUH KUALITAS PELAYANAN, KEPERCAYAAN, CITRA PERUSAHAAN TERHADAP LOYALITAS MEREK DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL MEDIASI PADA MASKAPAI GARUDA INDONESIA - Reyghana Louisrianda, Mirza Tabrani (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2017)
The purpose of this study is to investigate the influence of service quality, trust, corporate image towards brand loyalty with customer satisfaction as a mediating variable on Garuda Indonesia Airlines. The samples used in this study were 200 respondents who have used services of Garuda Indonesia. The sampling technique used was purposive sampling. Hierarchical Linear Modeling (HLM) was used as a method of analysis to investigate the influence of the variables involved. The results of this study showed that service quality, trust, and corporate image had a signficant influence towards customer satisfaction, which can in turn lead to brand loyalty. In addition, the results showed that the customer satisfaction variabel partially mediated the influence of the service quality and corporate image towards brand loyalty. Then, customer satisfaction variabel fully mediated the influence of the trust towards brand loyalty.Keywords: Service Quality, Trust, Corporate Image, Brand Loyalty, Customer Satisfaction